2016
DOI: 10.3390/jmse4040084
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Protein and Pigment Content in Two Chlorella Species Cultivated on Industrial Process Water

Abstract: Chlorella pyrenoidosa and Chlorella vulgaris were cultivated in pre-gasified industrial process water with high concentration of ammonia representing effluent from a local biogas plant. The study aimed to investigate the effects of growth media and cultivation duration on the nutritional composition of biomass. Variations in proteins, lipid, fatty acid composition, amino acids, tocopherols, and pigments were studied. Both species grew well in industrial process water. The contents of proteins were affected sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(39 citation statements)
references
References 31 publications
5
32
0
Order By: Relevance
“…The presence of essential amino acids (ESA) such as arginine, phenylalanine, histidine, isoleucine, leucine, lysine, methionine, threonine, and valine was found in the profile of C. vulgaris and fusant, except. This result is almost the same with study by Samek et al [34] which is found seven essential amino acid on Chlorella, while Safafar et al [35] found all the amino acid. This research was not found tryptophan in the amino acid profile on both experimented microalgae.…”
Section: Protein Content Of C Vulgaris and Fusantsupporting
confidence: 82%
“…The presence of essential amino acids (ESA) such as arginine, phenylalanine, histidine, isoleucine, leucine, lysine, methionine, threonine, and valine was found in the profile of C. vulgaris and fusant, except. This result is almost the same with study by Samek et al [34] which is found seven essential amino acid on Chlorella, while Safafar et al [35] found all the amino acid. This research was not found tryptophan in the amino acid profile on both experimented microalgae.…”
Section: Protein Content Of C Vulgaris and Fusantsupporting
confidence: 82%
“…Of all the carotenoids, lutein is the most abundant carotenoid in Chlorella cells (Safafar et al . ), with tendencies of accumulating up to 0.45% of dry weight cell (Borowitzka ). In some instances, lutein might account for about 0.2–0.5% of C. vulgaris biomass.…”
Section: Pigments and Their Applicationsmentioning
confidence: 99%
“…Chlorella vulgaris produces a high concentration of chlorophylls and carotenoids (Safafar et al 2016). The concentration of chlorophyll-a in Chlorella samples ranges from 2.5 to 17.5 mg g À1 dry weight (G€ ors et al 2009).…”
Section: Chlorophyll-a and Bmentioning
confidence: 99%
See 1 more Smart Citation
“…The protein content in the microalgal samples was determined by using a modified Micro-Biuret method described by Safafar et al [30].…”
Section: Protein Determinationmentioning
confidence: 99%